2022
DOI: 10.1186/s12875-022-01795-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of family-centered empowerment model on depression, anxiety, and stress of the family caregivers of patients with COVID-19: a randomized clinical trial

Abstract: Background Taking care of patients with Covid-19 is regarded as a challenging task for family caregivers. Hence, a Family-Centered Empowerment Model (FCEM) should help them achieve greater psychological strength throughout the home healthcare process. Methods This study is a randomized clinical trial with two groups; besides, pre-test and post-test designs were conducted based on the CONSORT checklist from April to July 2020, in Iran. Seventy famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The results of previous research by Mirzaei et al 15 also showed that approximately 80% of caregivers of COVID‐19 patients reported a severe level of care burden. A possible reason for the difference in outcomes is the increased awareness of those who care and support their family members who have COVID‐19 because of online group support, 20,30 community‐wide information, and social media. Obtaining such a finding in the present study indicates the positive effect of these interventions; however, there is still a need to implement appropriate interventions to reduce the burden of caring for someone with COVID‐19 within the community and network of caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of previous research by Mirzaei et al 15 also showed that approximately 80% of caregivers of COVID‐19 patients reported a severe level of care burden. A possible reason for the difference in outcomes is the increased awareness of those who care and support their family members who have COVID‐19 because of online group support, 20,30 community‐wide information, and social media. Obtaining such a finding in the present study indicates the positive effect of these interventions; however, there is still a need to implement appropriate interventions to reduce the burden of caring for someone with COVID‐19 within the community and network of caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The DASS-21 is a standard scale whose options are scored from 0 to 3. In this tool, seven items related to stress symptoms (2,6,8,11,12,14,18), seven items related to anxiety symptoms (1,4,7,7,15,19,20), and seven items related to depression symptoms (3,5,10,13,16,17,21). Scores 0-4 are mild, 5-11 are moderate, and more than 12 indicate severe psychological symptoms.…”
Section: Depression Anxiety and Stress Scale-21mentioning
confidence: 99%
See 1 more Smart Citation
“…and 10 studies were conducted by nurses. In addition, all the interventions were delivered in an offline format, except for one study in which the intervention used a combination of offline meetings and a mobile application (Nia et al, 2022). Eight studies (Dardouri et al, 2020;Deyhoul et al, 2020;Etemadifar et al, 2018;Izadpanah et al, 2021;Mohammadzadeh et al, 2022;Nia et al, 2022;Rabiei et al, 2020;Yeh et al, 2016) adopted the family centred empowerment model (FCEM)…”
Section: Most Of the Studies Involved Interventions By Health Profess...mentioning
confidence: 99%
“…7 Patients themselves must practice many non-pharmacological methods to improve their autonomy. [8][9][10] Non-pharmacological methods have fewer side effects and negative consequences than pharmacological treatments 11,12 ; the most widely used non-pharmacological methods are hydrotherapy, biofeedback, aromatherapy, meditation, massage, and acupuncture. 13,14 People usually use hydrotherapy for their relaxation and protection of their health.…”
Section: Introductionmentioning
confidence: 99%